Addressing an Imaginaray Companion in Ibn Muqbel,s poetry - Waqaf, Husein; Eid, Ruqaya (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research deals with technique of addressing an imaginary companion, being astylisttic phenomenan aiming at coloring Ibn Muqbel,s poetic discours, it is asudden shift frome one style to anther, serving muti- rhetorical purposes, and embodying the speaker,s sensation. Being a form of structur deviation whose specific funchion is detected in context its artistic feature, alse reflect on a recipient,s thoug contemplating this highlg aesthetic style. Addressing an imaginary conpanio can be Syntactic, Semantic and Syntactic-Semantic. This study looks into the syntactic forms of addressing an imaginary companion inrolved in changing the use of pronouns that preclude repeating antecedents, retrieving the meanings intended from poetic contexts.